True Science for Government Leaders and Educators: Obama’s U. S. Environmental Protection Agency Corruption - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2020)
The U.S. Environmental Protection Agency (EPA) 2014, 2015 ruling that coal fly ash is solid waste, not toxic waste, and thus can be dumped into landfills and rivers is a travesty against human and environmental health. The following EPA changes should be made: ● Coal fly ash must be deemed toxic waste, which it is; ● Dispersal of toxic coal fly ash into the environment must cease; ● Environment monitoring should be thorough, undertaken without prejudice, and include nano- and technologically created and/or modified substances; ● Research should be undertaken to find ways to extract valuable resources from coal fly ash (China extracts aluminum); and, ● The EPA must protect the environment, not purchase acquiescence through grant-giving. EPA grant-giving represents a direct conflict of interest and should cease. ● Aiding and abetting poisoning the air we breathe, the water we drink, and perverting the natural processes that make life on Earth possible is diabolically contrary to American principles expressed in the Declaration of Independence as “Safety and Happiness” and in the U. S. Constitution as “general Welfare.” The EPA, I posit, should be fundamentally changed to make human and environmental health its paramount priorities, or else the EPA should be legislated out of existence.